Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1978
DOI: 10.1128/jvi.26.2.306-315.1978
|View full text |Cite
|
Sign up to set email alerts
|

Abrogation of Fv-1b restriction with murine leukemia viruses inactivated by heat or by gamma irradiation

Abstract: Fv-lb restriction in BALB/3T3 cells is temporarily abrogated following infection with N-tropic murine leukemia virus. The mechanism of this phenomenon was investigated by comparing the inactivation rates for viral infectivity and for the ability of the same virus to abrogate Fv-1 restriction. Inactivation of the abrogating ability of N-tropic murine leukemia virus following graduated doses of gamma radiation proceeded at half the rate of that for viral infectivity. This result indicates that viral RNA must fun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
20
0

Year Published

1979
1979
2009
2009

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 37 publications
(22 citation statements)
references
References 21 publications
2
20
0
Order By: Relevance
“…The basic infectious center technique and the procedures for sequential infections in time-course experiments have been described before (Duran-Troise et ui., 1977). However, recent work has shown that N-tropic MuLV which has been inactivated at 43" C is quite efficient at abrogating Fv-lb restriction in BALB/3T3 cells (Bassin et al, 1978). We have therefore measured Fv-1 restriction in these experiments by a different technique from \ *\ 132 YE--, Mvcv *\ 0 that employed earlier (Duran-Troise et al, 1977): in place of fully infectious MuLV, we have used heat-inactivated MuLV as the " abrogating " virus, while fully infectious MuLV has replaced the corresponding MSV pseudotype as an " indicator " of cellular permissiveness.…”
Section: Infectious Center Techniquesmentioning
confidence: 99%
See 4 more Smart Citations
“…The basic infectious center technique and the procedures for sequential infections in time-course experiments have been described before (Duran-Troise et ui., 1977). However, recent work has shown that N-tropic MuLV which has been inactivated at 43" C is quite efficient at abrogating Fv-lb restriction in BALB/3T3 cells (Bassin et al, 1978). We have therefore measured Fv-1 restriction in these experiments by a different technique from \ *\ 132 YE--, Mvcv *\ 0 that employed earlier (Duran-Troise et al, 1977): in place of fully infectious MuLV, we have used heat-inactivated MuLV as the " abrogating " virus, while fully infectious MuLV has replaced the corresponding MSV pseudotype as an " indicator " of cellular permissiveness.…”
Section: Infectious Center Techniquesmentioning
confidence: 99%
“…A study of the abrogation of Fv-l restriction in various cell strains enables us to probe the mechanism of the cellular restriction process itself, since abrogation results from specific Fv-1 -mediated intracellular events following viral penetration of the non-permissive cells (Hudng et a/., 1973; Krontiris et a/., 1973). Since N-tropic virus heated at 43" C retains its ability to abrogate Fv-lb re-striction (Bassin et al, 1978), it serves as a convenient reagent with which to study the mechanism of Fv-1 restriction in various cells. We thsreforz tested the ability of heated virus preparations to abrogate Fv-1" restriction in DBA/2 czlls.…”
Section: Abrogation Of Fv-1" Restriction In Dbai2 C3ii Cells Followinmentioning
confidence: 99%
See 3 more Smart Citations